Problem Based Learning dalam Pembentukan Kemandirian Belajar Peserta Didik Kelas 3 SD - Tiara Ika Nor Khayati; Aries Tika Damayani; Kartinah Kartinah; Ranto Netty Sofiati (STKIP Andi Matappa Pangkep, 2023)
This study aims to describe the use of problem-based learning models in the formation of student learning independence. This research was conducted at SD Supriyadi 02 Semarang. The method used in this research is to use descriptive qualitative methods. The technique used in collecting data using observation and questionnaires / questionnaires containing 20 questions with 5 indicators. The question indicators include not depending on other people, self-confidence, responsibility, initiative and motivation. The results of the participants' responses as many as 28 respondents to the learning independence indicator were accumulated to get 94% results into the positive category, so that it can be said that the problem based learning model can shape the learning independence of grade 3 students at SD Supriyadi 02 Semarang.